KORELASI TINGKAT PENGETAHUAN MAHASISWA MENGENAI MARGA-MARGA BATAK TERHADAP PERILAKU NALILU DI FAKULTAS PERIKANAN DAN ILMU KELAUTAN - ", Yuvika; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Knowledge is the result out end this happened after people take action on a particular object.This study aims to determine the level of student knowledge marga-marga Batak to determinethe correlation between the level of knowlwdge od students about the marga-marga Batakagainst nalilu behavior. Marga is a group of unilinear kinship patrilinear, which would thebe passed on to offspring continuously. Nalilu is a condition in which a vagabond who doesnot know the clan and lineage, so he did not know where kinship and behave according to therules of life armpits surname. The research method used is quantitative and analyzed thecorrelation of product moment to compare the level knoeledge of students about the margamargaBatak on the behavior nalilu. The result of the student’s knowledge level clans Batakwas 57 (85%) of respondents in the medium category and 10 (15%) of respondents in the lowcategory. Nalilu behavior in the evironment as much as 6 (9%) respondents never do naliluand 46 (69%) sometimes never do nalilu and 15 (22%) of respondents have never donenalilu. Students who never did nalilu reasons if it met the hobo, it will immediately askwhether the people of his clan by clan related. If anything, call khinsip what to use. Inaddition, some students argued that they never intoduced clan. In this case means, they donot use rhe clan as her identy. Result of data analysis can be concluded that there is acorrelation between the level of knowledge of students about the clans hobo againts nalilubehavior with significant value 0.000 lebih kecil 0,05 and the degree of influence between thetwo variables that are in the strong category is 0.671.Keywords: Correlation, Knowledge, Marga, Nalilu